A community health support system for the planning of healthy cities - Gudes, Ori; Yigitcaniar, T.; Pathak, K. (Qut, 2009)
Communities are at the centre of concern for sustainable development, and they are entitled to a healthy and productive life, in harmony with the natural environment. Therefore, assuring equitable and effective health services through community and environmental health planning is an important factor for promoting sustainable development and constructing harmonious societies. Environmental and community health is crucial for the development of sustainable and healthy cities. One of the important pre-requisites of developing a sustainable and healthy city is a sound planning and development mechanism. This paper aims to investigate the challenges and opportunities of planning for healthy cities, and examine the effectiveness of participatory decision making systems in the development of healthy communities. It also introduces a recently developed methodology based on a web-based decision support system. This system contributes to solving environmental and community health problems, supports planning of healthy cities, and provides a powerful and effective platform for stakeholders and interested members of the community to confer with technicians, experts and decision makers. The primary focus is on the prospects and constraints of such a decision support system in improving community health behaviours, health planning, surveillance in urban communities, and environmental planning. The effectiveness of the web-based decision support system is measured by using the following yardsticks: increasing cooperation between stakeholders and the general public; improving the accuracy and quality of the decision-making process; and enhancing healthcare services of the locality. The paper tables the preliminary findings of the initial implementation of the decision support system in a pilot case study of the city of Logan, Australia, and concludes with future research directions.